2022
DOI: 10.1002/eer2.7
|View full text |Cite
|
Sign up to set email alerts
|

Life‐cycle seismic fragility of a cable‐stayed bridge considering chloride‐induced corrosion

Abstract: The coastal or sea‐crossing bridges located in seismic regions are experiencing long‐term chloride‐induced corrosion in their life cycles and have a high risk of suffering from strong earthquakes. Thus, the fragilities of these bridges must be properly evaluated under the multiple hazards of corrosion and earthquake. Conventional fragility assessment requires expensive computational efforts despite extensive applications in previous research. To this end, this paper proposes a life‐cycle fragility analysis fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Due to the rapid economic development of urbanization in China over the last decades, many urban infrastructures have been constructed, such as buildings, highways, bridges, tunnels, and so on [1][2][3]. All these structures should be designed and constructed under the sustainable and resilience concept [4][5][6] to ensure functionality and safety during the life-cycle service.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rapid economic development of urbanization in China over the last decades, many urban infrastructures have been constructed, such as buildings, highways, bridges, tunnels, and so on [1][2][3]. All these structures should be designed and constructed under the sustainable and resilience concept [4][5][6] to ensure functionality and safety during the life-cycle service.…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al [ 12 ] established a fragility analysis framework for RC bridge structures subjected to the multi-hazard effect of vessel collisions and corrosion. Meanwhile, the modeling and analysis of the time-dependent seismic fragility due to the corrosion effects of RC bridges has received significant attention [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to China’s Ministry of Transportation, the aging and deterioration phenomenon of MSC concrete girder bridges are commonly found in seismic zones, such as northern China, because deicing salts are extensively used on highway bridges [ 24 ]. The existing contributions [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] also indicated that RC bridges subjected to the mechanisms of corrosion deterioration might be more vulnerable to earthquake hazards. Moreover, since previous studies [ 25 , 26 ] demonstrated that chloride from deicing salts can cause more degradation of bridges than that in a marine environment, the impacts of corrosion degradation due to chloride-laden deicing salts should be researched in detail.…”
Section: Introductionmentioning
confidence: 99%